PENERAPAN SISTEM INFORMASI MANAJEMEN UNTUK MENJALIN KERJASAMA DENGAN WALI MURID - Zakia, Hanifa; Hadiyanto, Hadiyanto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This research found out the implementation of management information systems in SMP N 1 Talamau. We used qualitative research methods. The result showed that the existing management information system meets standards, both in terms of students, curriculum, human resources, facilities and quality of users, who are able to manage the activities that exist in schools. Then, the role of parents is also important in implementing management information systems to improve the quality of education in SMP N 1 Talamau, implementing special strategies that utilize information technology-based management information systems, namely information and consultation rooms that function as a center for consultation between schools and parents in providing access to parents to see the development of students' academic values.